Unveiling the role of O(6)-methylguanine-DNA methyltransferase in cancer therapy: insights into alkylators, pharmacogenomics, and others - Chen, Lizhen; Wen, Alex (Frontiers in Oncology, 2024)
Cancer chemotherapy is advancing as we understand how cellular mechanisms and drugs interact, particularly involving the enzyme MGMT, which repairs DNA damage that can cause cancer. This review examines MGMT's role in DNA repair, its impact on chemotherapy, and its complex interaction with radiation therapy. MGMT activity can both protect against mutations and cause drug resistance. Modulating MGMT could improve treatment efficacy and tailoring therapy to MGMT status may enhance patient outcomes. Understanding MGMT is crucial for developing precise cancer treatments and advancing patient care.